Redistributive fiscal policies and regional economic disparities - Bankole Fred Olayele; Kwok Tong Soo (Cogent Economics & Finance, 2020)
Finding a definitive answer to the question of whether fiscal redistribution is harmful or beneficial for regional economic performance is not straightforward. This paper disentangles the key components of fiscal redistribution in a regional Canada-US setting. Redistributive spending is calibrated as the difference between pretax personal income, and personal income after federal taxes and transfers. Based largely on fixed effects and dynamic panel methods, our findings support the battery of studies on the mixed evidence concerning the relationship between fiscal redistribution and per capita income. To the extent that results are sensitive to estimation methods and functional specifications, the study underscores the importance of unbundling the components of a redistributive fiscal package in a bid to establish optimal thresholds for effective policy interventions.
Keywords: H23; H3; H77; R11; 330; federalism; fiscal policies; redistribution; regional economy